The Effect of Financial Literacy, Financial Attitude, and Lifestyle on Saving Behavior among Generation Z in Pontianak with Self-Control as a Moderating Variable - Sabrina Nabila Ajmi; Fuad Ramdhan Ryanto (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to analyze the effect of Financial Literacy, Financial Attitude, and Lifestyle on Saving Behavior with Self Control as a moderating variable among Generation Z in Pontianak City. The research method used is quantitative with moderated regression analysis (Moderated Regression Analysis/MRA). The research sample consisted of 150 Generation Z respondents aged 15–29 years who were selected using purposive sampling technique. Data collection was conducted through a questionnaire measured using a Likert scale, then processed using SPSS software version 25. The results show that all research instruments met the validity requirement with r count > 0.160 and reliability with Cronbach's Alpha > 0.60. The regression model has met the classical assumption tests including normality, multicollinearity, and linearity. Simultaneously, Financial Literacy, Financial Attitude, and Lifestyle have a significant effect on Saving Behavior. Partially, Financial Literacy, Financial Attitude, and Lifestyle on Saving Behavior. However, Self Control does not have a significant direct effect on Saving Behavior. Nevertheless, Self Control is proven to significantly moderate the effect of Financial Literacy (sig. 0.000), Financial Attitude (sig. 0.007), and Lifestyle (sig. 0.006) on Saving Behavior. The coefficient of determination (R²) value of 0.519 indicates that 51.9% of the variation in Saving Behavior can be explained by the independent variables in this study. The findings of this study provide practical implications that to improve saving behavior among Generation Z in Pontianak City, it is necessary to pay attention to aspects of financial literacy, financial attitude, and lifestyle management, by considering the role of Self Control as a factor that can strengthen or weaken the influence of these three variables on saving behavior.